LO01: Prevalence of pulmonary embolism among Canadian emergency department patients with syncope: a multicenter prospective cohort study. (15th May 2017) - Thiruganasambandamoorthy, V.; Sivilotti, M.; McRae, A.; Mukarram, M.A.; Kim, S.; Rowe, B.H.; Huang, L.
Abstract : Introduction: A recent cross-sectional study reported a 17.3% prevalence of pulmonary embolism (PE) among patients with syncope. However, the study had several flaws including spectrum and work-up bias with over-diagnosis due to excessive investigations. We sought to evaluate the prevalence of PE among Canadian emergency department (ED) patients presenting with syncope.Methods: We enrolled adults with syncope at 5 EDs and collected demographics, proportion of patients evaluated for suspected PE, their Wells PE score values and results of investigations [d-dimer, computed angiography (CT) of chest or ventilation-perfusion (VQ) scan]. 30-day adjudicated outcome included diagnosis of PE requiring treatment. We used descriptive statistics to report the results.Results: 4, 739 patients [mean age 54.3 years, 54.4% females, and 587 (12.4%) hospitalized] were enrolled. 323 patients (6.8%) had further evaluation and investigations performed for suspected PE: 255 patients had D-dimer performed, 140 had CT chest and 17 had VQ performed. Of the 323 patients, 300 patients were low risk (Wells score ≤4) and 23 were high-risk (score >4). A total of 16 patients (0.3%) in the study cohort were diagnosed with PE: 10 patients were diagnosed in the ED, 5 patients were diagnosed while hospitalized as inpatient, and 1 patient was diagnosed on a return ED visit. Overall the prevalence of PE was 0.3% among all ED patients with syncope; and a 0.9% among those hospitalized for syncope.Conclusion: Our study shows that the prevalence of PE is very low among all patients presenting to the ED with syncope. The prevalence is also very low among those hospitalized for syncope than previously reported. While PE should be suspected and further investigations performed among syncope patients if clinically appropriate, caution should also be taken against indiscriminate over-investigations for PE.